Non-aqueous electrolyte secondary battery

JP7638247B2Active Publication Date: 2025-03-03PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022146424
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-09-14
Publication Date
2025-03-03
Estimated Expiration
2042-09-14

Smart Images

  • Figure 0007638247000003
    Figure 0007638247000003
  • Figure 0007638247000004
    Figure 0007638247000004
  • Figure 0007638247000001
    Figure 0007638247000001
Patent Text Reader

Abstract

To provide a nonaqueous electrolyte secondary battery having both high output characteristics and high capacity deterioration resistance in repetitive charge and discharge with a large current.SOLUTION: A nonaqueous electrolyte secondary battery disclosed herein includes a positive electrode, a negative electrode, and a nonaqueous electrolyte. The positive electrode includes a positive electrode current collector and a positive electrode active material layer supported by the positive electrode current collector. The positive electrode active material layer contains a positive electrode active material and carbon nanotubes. The nonaqueous electrolyte contains a nonaqueous solvent and a supporting electrolyte. The nonaqueous solvent contains 2 to 9 volume % of carboxylate ester that has 6 or less carbon atoms and may be substituted by a fluorine atom.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-aqueous electrolyte secondary battery. [Background technology]

[0002] 2. Description of the Related Art In recent years, nonaqueous electrolyte secondary batteries such as lithium ion secondary batteries have been suitably used as portable power sources for personal computers, mobile terminals, and the like, and as power sources for driving vehicles such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs), among others.

[0003] Recently, the demand for HEVs has been rapidly increasing, and there is a demand for further improvement in the performance of secondary batteries for driving power sources of HEVs. In the positive electrode of a nonaqueous electrolyte secondary battery as a secondary battery for driving power sources of HEVs, a positive electrode active material and acetylene black as a conductive material are generally used. In addition, in the nonaqueous electrolyte of a nonaqueous electrolyte secondary battery as a secondary battery for driving power sources of HEVs, carbonates are generally used as a nonaqueous solvent. Meanwhile, it is known that a carboxylate ester can be used as the nonaqueous solvent (for example, see Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2002-305035 A Summary of the Invention [Problem to be solved by the invention]

[0005] In order to improve the performance of secondary batteries for driving power sources of HEVs, it is particularly desirable to increase the output and improve resistance to capacity degradation when repeatedly charged and discharged at a large current. In particular, HEVs are characterized in that the secondary batteries for driving power sources are repeatedly charged and discharged within a narrow SOC range. However, as a result of intensive research by the present inventors, it has been found that the nonaqueous electrolyte secondary batteries of the prior art cannot adequately meet the recent increasing demands for higher output and improved resistance to capacity degradation when repeatedly charged and discharged at a large current.

[0006] SUMMARY OF THE PRESENT EMBODIMENTS The present invention has an object to provide a non-aqueous electrolyte secondary battery that is excellent in both output characteristics and resistance to capacity degradation when repeatedly charged and discharged at a large current. [Means for solving the problem]

[0007] The nonaqueous electrolyte secondary battery disclosed herein includes a positive electrode, a negative electrode, and a nonaqueous electrolyte. The positive electrode includes a positive electrode current collector and a positive electrode active material layer supported by the positive electrode current collector. The positive electrode active material layer contains a positive electrode active material and carbon nanotubes. The nonaqueous electrolyte includes a nonaqueous solvent and a supporting salt. The nonaqueous solvent contains 2 to 9 volume % of a carboxylic acid ester having 6 or less carbon atoms which may be substituted with a fluorine atom.

[0008] According to this configuration, it is possible to provide a nonaqueous electrolyte secondary battery that is excellent in both output characteristics and resistance to capacity degradation when repeatedly charged and discharged at a large current. [Brief description of the drawings]

[0009] [Figure 1] 1 is a cross-sectional view showing a schematic internal structure of a lithium-ion secondary battery according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic exploded view showing the configuration of a wound electrode body of a lithium ion secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Matters not mentioned in this specification but necessary for carrying out the present invention can be understood as design matters for a person skilled in the art based on the prior art in the relevant field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense in the relevant field. In addition, in the following drawings, members and parts having the same function are described with the same reference numerals. Furthermore, the dimensional relationships (length, width, thickness, etc.) in each drawing do not reflect the actual dimensional relationships. In addition, the numerical range expressed as "A to B" in this specification includes A and B.

[0011] In this specification, the term "secondary battery" refers to an electricity storage device that can be repeatedly charged and discharged, and includes so-called storage batteries and electricity storage elements such as electric double layer capacitors. In addition, in this specification, the term "lithium ion secondary battery" refers to a secondary battery that uses lithium ions as a charge carrier and realizes charging and discharging by the transfer of charge associated with the lithium ions between the positive and negative electrodes.

[0012] Hereinafter, the present invention will be described in detail using as an example a flat rectangular lithium ion secondary battery having a flat wound electrode body and a flat battery case, but it is not intended that the present invention be limited to the embodiment described therein.

[0013] The lithium ion secondary battery 100 shown in FIG. 1 is a sealed battery constructed by housing a flat wound electrode body 20 and a nonaqueous electrolyte 80 in a flat rectangular battery case (i.e., an outer container) 30. The battery case 30 is provided with a positive electrode terminal 42 and a negative electrode terminal 44 for external connection, and a thin-walled safety valve 36 that is set to release the internal pressure when the internal pressure of the battery case 30 rises to a predetermined level or higher. The battery case 30 is also provided with an injection port (not shown) for injecting the nonaqueous electrolyte 80. The positive electrode terminal 42 is electrically connected to the positive electrode current collector plate 42a. The negative electrode terminal 44 is electrically connected to the negative electrode current collector plate 44a. The material of the battery case 30 is, for example, a lightweight metal material with good thermal conductivity, such as aluminum. Note that FIG. 1 does not accurately represent the amount of the nonaqueous electrolyte 80.

[0014] 1 and 2, the wound electrode body 20 has a configuration in which a positive electrode sheet 50 and a negative electrode sheet 60 are overlapped with two long separator sheets 70 interposed therebetween and wound in the longitudinal direction. The positive electrode sheet 50 has a configuration in which a positive electrode active material layer 54 is formed along the longitudinal direction on one or both sides (both sides here) of a long positive electrode current collector 52. The negative electrode sheet 60 has a configuration in which a negative electrode active material layer 64 is formed along the longitudinal direction on one or both sides (both sides here) of a long negative electrode current collector 62. The positive electrode active material layer-free portion 52a (i.e., a portion where the positive electrode active material layer 54 is not formed and the positive electrode current collector 52 is exposed) and the negative electrode active material layer-free portion 62a (i.e., a portion where the negative electrode active material layer 64 is not formed and the negative electrode current collector 62 is exposed) are formed so as to protrude outward from both ends in the winding axis direction (i.e., the sheet width direction perpendicular to the longitudinal direction) of the wound electrode body 20. The positive electrode active material layer-free portion 52a and the negative electrode active material layer-free portion 62a are joined to the positive electrode current collector 42a and the negative electrode current collector 44a, respectively.

[0015] The ratio of the area of ​​the main surface of the negative electrode active material layer 64 to the area of ​​the main surface of the positive electrode active material layer 54 is preferably 1.05 to 1.15.

[0016] The positive electrode current collector 52 constituting the positive electrode sheet 50 may be a known positive electrode current collector used in lithium ion secondary batteries, and examples thereof include a sheet or foil made of a metal having good electrical conductivity (e.g., aluminum, nickel, titanium, stainless steel, etc.). The positive electrode current collector 52 is preferably aluminum foil.

[0017] The dimensions of the positive electrode current collector 52 are not particularly limited and may be appropriately determined depending on the battery design. When an aluminum foil is used as the positive electrode current collector 52, the thickness is not particularly limited, but is, for example, 5 μm or more and 35 μm or less, and preferably 7 μm or more and 20 μm or less.

[0018] The positive electrode active material layer 54 contains a positive electrode active material and carbon nanotubes (CNTs). As the positive electrode active material, a known positive electrode active material used in a lithium ion secondary battery may be used. Specifically, for example, as the positive electrode active material, a lithium composite oxide, a lithium transition metal phosphate compound, or the like may be used. The crystal structure of the positive electrode active material is not particularly limited, and may be a layered structure, a spinel structure, an olivine structure, or the like.

[0019] The lithium composite oxide is preferably a lithium transition metal composite oxide containing at least one of Ni, Co, and Mn as a transition metal element, and specific examples thereof include lithium nickel-based composite oxides, lithium cobalt-based composite oxides, lithium manganese-based composite oxides, lithium nickel manganese-based composite oxides, lithium nickel cobalt manganese-based composite oxides, lithium nickel cobalt aluminum-based composite oxides, and lithium iron nickel manganese-based composite oxides.

[0020] In this specification, the term "lithium nickel cobalt manganese composite oxide" includes oxides containing Li, Ni, Co, Mn, and O as constituent elements, as well as oxides containing one or more additional elements other than those. Examples of such additional elements include transition metal elements and typical metal elements such as Mg, Ca, Al, Ti, V, Cr, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Fe, Zn, and Sn. The additional element may be a semimetal element such as B, C, Si, or P, or a nonmetal element such as S, F, Cl, Br, or I. This also applies to the above-mentioned lithium nickel composite oxide, lithium cobalt composite oxide, lithium manganese composite oxide, lithium nickel manganese composite oxide, lithium nickel cobalt aluminum composite oxide, and lithium iron nickel manganese composite oxide.

[0021] Examples of the lithium transition metal phosphate compound include lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), and lithium manganese iron phosphate.

[0022] These positive electrode active materials may be used alone or in combination of two or more. As the positive electrode active material, lithium nickel cobalt manganese based composite oxide is particularly preferable because of its excellent properties such as initial resistance characteristics.

[0023] The average particle diameter (median diameter: D50) of the positive electrode active material is not particularly limited, but is, for example, 0.05 μm to 25 μm, preferably 1 μm to 20 μm, and more preferably 3 μm to 15 μm. The average particle diameter (D50) of the positive electrode active material can be determined, for example, by a laser diffraction scattering method.

[0024] The content of the positive electrode active material in the positive electrode active material layer 54 (i.e., the content of the positive electrode active material relative to the total mass of the positive electrode active material layer 54) is not particularly limited, but is, for example, 80 mass% or more, preferably 87 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, and most preferably 97 mass% or more.

[0025] In this embodiment, CNT is used as the conductive material of the positive electrode active material layer 54. The CNT is usually dispersed in the form of a single particle and / or aggregate together with the positive electrode active material in the positive electrode active material layer 54. The CNT can improve the conductivity of the positive electrode active material layer 54, and can increase the output of the lithium ion secondary battery 100. In this embodiment, the CNT is used in combination with a specific amount of carboxylate. This can further increase the output of the lithium ion secondary battery 100, and in addition, can significantly increase the capacity degradation resistance when the lithium ion secondary battery 100 is repeatedly charged and discharged at a large current. This is believed to be due to the following reasons.

[0026] The carboxylate ester having a small number of carbon atoms has the effect of lowering the viscosity of the nonaqueous electrolyte 80. Here, by using the carboxylate ester having a small number of carbon atoms in combination with CNT, which is the conductive material of the positive electrode active material layer 54, it is possible to improve the wettability between the positive electrode active material layer 54 and the nonaqueous electrolyte 80 (i.e., the ease with which the nonaqueous electrolyte 80 adheres to the components of the positive electrode active material layer 54). It is believed that the improvement in wettability is due to the fact that the CNT has a hollow cylindrical structure, and the nonaqueous solvent such as the carboxylate ester penetrates into the hollow portion, so that the hollow portion can also be used for the flow of the nonaqueous electrolyte 80.

[0027] The output resistance can be reduced by improving the wettability between the positive electrode active material layer 54 and the nonaqueous electrolyte solution 80. In addition, the improved wettability improves the uniformity of charge and discharge during charge and discharge cycles at a large current, and suppresses capacity degradation when charge and discharge are repeated at a large current.

[0028] The type of CNT used is not particularly limited, and for example, single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT), multi-walled carbon nanotubes (MWCNT), etc. can be used. These can be used alone or in combination of two or more. The CNT may be manufactured by an arc discharge method, a laser ablation method, a chemical vapor deposition method, etc. In general, MWCNT has a larger inner diameter than SWCNT. Therefore, since it is easier to flow the nonaqueous electrolyte 80 through the hollow part of the CNT, MWCNT is preferable as the CNT.

[0029] The average length of the CNTs is not particularly limited. If the average length of the CNTs is too long, the CNTs tend to aggregate and the dispersibility tends to decrease. In addition, Li ions diffusing inside the CNTs are difficult to come out of the CNTs. Therefore, the average length of the CNTs is preferably 15 μm or less, more preferably 8.0 μm or less, and even more preferably 5.0 μm or less. On the other hand, if the average length of the CNTs is too short, it becomes difficult for the CNTs to cover the surface of the positive electrode active material, and it tends to be difficult to form a conductive path between the positive electrode active materials. Therefore, the average length of the CNTs is preferably 0.1 μm or more.

[0030] The average diameter of the CNT is not particularly limited, and is, for example, 0.1 nm to 150 nm. Since the nonaqueous electrolyte 80 can easily flow through the hollow portion of the CNT, the average diameter of the CNT is preferably 1.0 nm or more, and more preferably 2.0 nm or more. On the other hand, if the average diameter of the CNT is too large, the flexibility of the CNT particles decreases and the shape becomes closer to a rod shape, making it difficult for the CNT to cover the positive electrode active material. As a result, there is a risk that the degree of improvement in wettability of the surface of the positive electrode active material will be reduced. Therefore, the average diameter of the CNT is preferably 100 nm or less, and more preferably 50 nm or less.

[0031] The average length and average diameter of CNTs can be obtained, for example, by taking an electron microscope photograph of CNTs and averaging the lengths and diameters of 100 or more CNTs. Specifically, for example, a CNT dispersion is diluted and then dried to prepare a measurement sample. This sample is observed with a scanning electron microscope (SEM) to obtain the lengths and diameters of 100 or more CNTs and calculate the average value. At this time, if the CNTs are re-aggregated, the length and diameter are obtained for the bundle of aggregated CNTs.

[0032] Typically, only CNTs are used as the conductive material of the positive electrode active material layer 54. However, the positive electrode active material layer 54 may contain a conductive material other than CNTs (e.g., carbon black, etc.) within a range that does not significantly impair the effects of the present invention.

[0033] The CNT content in the positive electrode active material layer 54 is not particularly limited. If the CNT content in the positive electrode active material layer 54 is too small, the above-mentioned effects may be reduced. On the other hand, if the CNT content is too large, there is a risk of the thickening of the positive electrode slurry and the decrease in the impregnation of the positive electrode active material layer 54 with the nonaqueous electrolyte solution 80 during the manufacture of the lithium-ion secondary battery 100. Therefore, the CNT content in the positive electrode active material layer 54 is preferably 0.1% by mass to 3.0% by mass, more preferably 0.3% by mass to 2.5% by mass, and even more preferably 0.5% by mass to 2.0% by mass.

[0034] The positive electrode active material layer 54 may contain components other than the positive electrode active material, such as trilithium phosphate, a binder, a carbon nanotube dispersant (CNT dispersant), etc. As the binder, for example, polyvinylidene fluoride (PVdF) or the like can be used.

[0035] Examples of CNT dispersants that can be used include surfactant-type dispersants (also called low molecular weight dispersants), polymer-type dispersants, and inorganic-type dispersants. The CNT dispersant may be anionic, cationic, amphoteric, or nonionic. Thus, the CNT dispersant may have at least one functional group selected from the group consisting of anionic groups, cationic groups, and nonionic groups in its molecular structure. The surfactant refers to an amphiphilic substance having a chemical structure in which a hydrophilic portion and a lipophilic portion are bonded together by a covalent bond in the molecular structure.

[0036] Specific examples of CNT dispersants include polycondensation aromatic surfactants such as sodium salt of naphthalenesulfonic acid formalin condensate, ammonium salt of naphthalenesulfonic acid formalin condensate, and sodium salt of methylnaphthalenesulfonic acid formalin condensate; polycarboxylic acids and their salts, such as polyacrylic acid and its salts, polymethacrylic acid and its salts; triazine derivative dispersants (preferably containing a carbazolyl group or a benzimidazolyl group); polyvinylpyrrolidone (PVP); polymers having polynuclear aromatics such as pyrene and anthracene in the side chain; polynuclear aromatic ammonium derivatives such as pyrene ammonium derivatives (e.g., compounds in which an ammonium bromide group is introduced into pyrene) and anthracene ammonium derivatives; and the like. These CNT dispersants can be used alone or in combination of two or more. As the CNT dispersant, those containing polynuclear aromatics are preferable. Specifically, as the CNT dispersant, polymers having polynuclear aromatics in the side chain and polynuclear aromatic ammonium derivatives are preferable.

[0037] The content of trilithium phosphate in the positive electrode active material layer 54 is not particularly limited, but is preferably from 1 to 15% by mass, and more preferably from 2 to 12% by mass. The content of the binder in the positive electrode active material layer 54 is not particularly limited, but is preferably from 0.1 to 10% by mass, more preferably from 0.2 to 5% by mass, and even more preferably from 0.3 to 2% by mass.

[0038] The amount of the CNT dispersant may be appropriately determined depending on the type of CNT and CNT dispersant. Here, if the ratio of the CNT dispersant is too small, dispersibility may be insufficient. On the other hand, if the ratio of the CNT dispersant is too large, the CNT dispersant may adhere excessively to the CNT surface, causing an increase in resistance. When the CNT is SWCNT, the amount of the CNT dispersant used is, for example, 1 part by mass to 400 parts by mass, preferably 20 parts by mass to 200 parts by mass, relative to 100 parts by mass of CNT. When the CNT is MWNT, the amount of the CNT dispersant used is, for example, 1 part by mass to 100 parts by mass, preferably 4 parts by mass to 40 parts by mass, relative to 100 parts by mass of CNT.

[0039] The thickness of the positive electrode active material layer 54 is not particularly limited, but is, for example, from 10 μm to 300 μm, and preferably from 20 μm to 200 μm.

[0040] The positive electrode sheet 50 may contain an insulating layer (not shown) at the boundary between the positive electrode active material layer non-forming portion 52a and the positive electrode active material layer 54. The insulating layer contains, for example, ceramic particles.

[0041] The negative electrode current collector 62 constituting the negative electrode sheet 60 may be a known negative electrode current collector used in lithium ion secondary batteries, and examples thereof include a sheet or foil made of a metal having good electrical conductivity (e.g., copper, nickel, titanium, stainless steel, etc.). Copper foil is preferable as the negative electrode current collector 62.

[0042] The dimensions of the negative electrode current collector 62 are not particularly limited and may be appropriately determined depending on the battery design. When a copper foil is used as the negative electrode current collector 62, the thickness is not particularly limited, but is, for example, 5 μm or more and 35 μm or less, and preferably 6 μm or more and 20 μm or less.

[0043] The negative electrode active material layer 64 contains a negative electrode active material. As the negative electrode active material, for example, a carbon material such as graphite, hard carbon, soft carbon, etc. The graphite may be natural graphite or artificial graphite, or may be amorphous carbon-coated graphite in which graphite is coated with an amorphous carbon material.

[0044] The average particle diameter (median diameter: D50) of the negative electrode active material is not particularly limited, but is, for example, 0.1 μm to 50 μm, preferably 1 μm to 25 μm, and more preferably 5 μm to 20 μm. The average particle diameter (D50) of the negative electrode active material can be determined, for example, by a laser diffraction scattering method.

[0045] The negative electrode active material layer 64 may contain components other than the active material, such as a binder, a thickener, etc. As the binder, for example, styrene butadiene rubber (SBR), polyvinylidene fluoride (PVdF), etc. may be used. As the thickener, for example, carboxymethyl cellulose (CMC), etc. may be used.

[0046] The content of the negative electrode active material in the negative electrode active material layer 64 is preferably 90% by mass or more, and more preferably 95% by mass or more and 99% by mass or less. The content of the binder in the negative electrode active material layer 64 is preferably 0.1% by mass or more and 8% by mass or less, and more preferably 0.5% by mass or more and 3% by mass or less. The content of the thickener in the negative electrode active material layer 64 is preferably 0.3% by mass or more and 3% by mass or less, and more preferably 0.5% by mass or more and 2% by mass or less.

[0047] The thickness of the negative electrode active material layer 64 is not particularly limited, but is, for example, not less than 10 μm and not more than 400 μm, and preferably not less than 20 μm and not more than 300 μm.

[0048] The separator 70 may be a porous sheet (film) made of a resin such as polyethylene (PE), polypropylene (PP), polyester, cellulose, or polyamide. Such a porous sheet may have a single-layer structure or a laminated structure of two or more layers (for example, a three-layer structure in which a PP layer is laminated on both sides of a PE layer). A heat-resistant layer (HRL) containing ceramic particles or the like may be provided on the surface of the separator 70.

[0049] The thickness of the separator 70 is not particularly limited, but is, for example, 5 μm to 50 μm, and preferably 10 μm to 30 μm. The air permeability of the separator 70 obtained by the Gurley test method is not particularly limited, but is preferably 350 sec / 100 cc or less.

[0050] The non-aqueous electrolyte 80 contains a non-aqueous solvent and a supporting salt. In this embodiment, the non-aqueous solvent contains a predetermined amount of a carboxylic acid ester having 6 or less carbon atoms which may be substituted with a fluorine atom.

[0051] The carboxylic acid ester having 6 or less carbon atoms acts to reduce the viscosity of the nonaqueous electrolyte solution 80. As described above, by combining the carboxylic acid ester having 6 or less carbon atoms with CNTs as the conductive material of the positive electrode 50, the output of the lithium ion secondary battery 100 can be significantly increased, and in addition, the resistance to capacity degradation when the lithium ion secondary battery 100 is repeatedly charged and discharged at a large current can be significantly increased.

[0052] Examples of carboxylates having 6 or less carbon atoms which may be substituted with a fluorine atom include acetates such as methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl difluoroacetate, ethyl trifluoroacetate, difluoromethyl acetate, trifluoroethyl acetate, and vinyl acetate; propionates such as methyl propionate, ethyl propionate, propyl propionate, and vinyl propionate; and butanoates such as methyl butanoate and ethyl butanoate.

[0053] Since the carboxylate ester easily enters the hollow space of the CNT, the number of carbon atoms of the carboxylate ester is preferably 4 or less, more preferably 3 or less. In addition, the carboxylate ester is preferably not substituted with a fluorine atom. The carboxylate ester is particularly preferably methyl acetate.

[0054] If the content of the carboxylate in the non-aqueous solvent is too low, the output improvement effect is insufficient. Therefore, the content of the carboxylate in the non-aqueous solvent is 2% by volume or more, preferably 3% by volume or more, and more preferably 5% by volume or more. On the other hand, if the content of the carboxylate in the non-aqueous solvent is too high, the effect of improving the capacity deterioration resistance when the lithium ion secondary battery 100 is repeatedly charged and discharged at a large current is insufficient. Therefore, the content of the carboxylate in the non-aqueous solvent is 9% by volume or less, preferably 8.5% by volume or less, more preferably 8% by volume or less, and even more preferably 7% by volume or less.

[0055] The non-aqueous solvent includes an organic solvent other than carboxylate ester. Examples of the organic solvent include carbonates, ethers, nitriles, sulfones, lactones, etc., and among them, carbonates are preferred. Examples of carbonates include ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyl difluoromethyl carbonate (F-DMC), trifluorodimethyl carbonate (TFDMC), etc. Such organic solvents can be used alone or in appropriate combination of two or more.

[0056] The non-aqueous electrolyte 80 may contain a supporting salt (in other words, an electrolyte salt). As the supporting salt, for example, a lithium salt such as LiPF6, LiBF4, or lithium bis(fluorosulfonyl)imide (LiFSI) (preferably LiPF6) can be suitably used. The concentration of the supporting salt is preferably 0.7 mol / L or more and 1.3 mol / L or less.

[0057] In addition, the nonaqueous electrolyte 80 may contain various additives other than the above-mentioned components, such as film-forming agents such as vinylene carbonate (VC) and oxalate complexes; gas generating agents such as biphenyl (BP) and cyclohexylbenzene (CHB); and thickeners, so long as the effects of the present invention are not significantly impaired.

[0058] The lithium ion secondary battery 100 is excellent in both output characteristics and resistance to capacity degradation when repeatedly charged and discharged at a large current. Therefore, the lithium ion secondary battery 100 has high output and durability. The lithium ion secondary battery 100 can be used for various applications. Suitable applications include a driving power source mounted on a vehicle such as an electric vehicle (BEV), a hybrid vehicle (HEV), and a plug-in hybrid vehicle (PHEV). The lithium ion secondary battery 100 can also be used as a storage battery for a small power storage device or the like. Here, it is desired that the driving power source for an HEV is excellent in both output characteristics and resistance to capacity degradation when repeatedly charged and discharged at a large current. Furthermore, the lithium ion secondary battery 100 is particularly excellent in resistance to capacity degradation when repeatedly charged and discharged at a large current in a narrow SOC range. Therefore, a particularly suitable application of the lithium ion secondary battery 100 is a driving power source for an HEV. The lithium ion secondary battery 100 can also be used in the form of a battery pack typically formed by connecting a plurality of batteries in series and / or in parallel.

[0059] The above describes, as an example, a rectangular lithium ion secondary battery 100 equipped with a flat wound electrode assembly 20. However, the lithium ion secondary battery can also be configured as a lithium ion secondary battery equipped with a laminated electrode assembly (i.e., an electrode assembly in which multiple positive electrodes and multiple negative electrodes are alternately laminated). The lithium ion secondary battery can also be configured as a cylindrical lithium ion secondary battery, a laminated case type lithium ion secondary battery, etc.

[0060] The secondary battery according to this embodiment can be constructed as a non-aqueous electrolyte secondary battery other than a lithium ion secondary battery in accordance with a known method.

[0061] Examples of the present invention will be described in detail below, but it is not intended that the present invention be limited to those shown in these examples.

[0062] [Examples 1 to 4 and Comparative Examples 1 to 5] LiNi as a positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3 O2, a conductive material, and PVdF as a binder were mixed in a mass ratio of active material:conductive material:PVdF=97.5:1.5:1.0. In Examples 1 to 4 and Comparative Examples 1 and 2, MWCNT (average diameter 15 nm, average length 0.5 μm) was used as the conductive material. In Comparative Examples 3 to 5, acetylene black (AB: average particle diameter 35 nm, average aggregate diameter 1 μm) was used.

[0063] An appropriate amount of N-methyl-2-pyrrolidone was added to the mixture to prepare a positive electrode slurry. The positive electrode slurry was applied to both sides of an aluminum foil having a thickness of 12 μm as a positive electrode current collector. At this time, a positive electrode slurry uncoated portion was provided on the aluminum foil as a lead connection portion. The amount of the positive electrode slurry applied was set so that the basis weight of the positive electrode active material layer formed was 11 mg / cm2 in total on both sides. 2 It was adjusted so that

[0064] The applied slurry was dried to form a positive electrode active material layer. The obtained sheet was pressed with a roller to adjust the porosity of the positive electrode active material layer to 40 volume %. The porosity of the positive electrode active material layer was measured with a mercury porosimeter. This was cut to a predetermined size to obtain a positive electrode in which a positive electrode active material layer was formed on both sides of the positive electrode current collector.

[0065] Graphite as a carbon-based negative electrode active material, sodium salt of carboxymethylcellulose (CMC-Na), and a dispersion of styrene butadiene rubber (SBR) were mixed in a solid mass ratio of graphite:CMC-Na:CMC=98:1:1. An appropriate amount of ion-exchanged water was further added to prepare a negative electrode slurry. The negative electrode slurry was applied to both sides of a copper foil with a thickness of 8 μm as a negative electrode current collector. At this time, a negative electrode slurry uncoated portion was provided on the copper foil as a lead connection portion.

[0066] The applied paste was dried to form a negative electrode active material layer. The obtained sheet was pressed with a roller and then cut to a predetermined size to obtain a negative electrode in which a negative electrode active material layer was formed on both sides of the negative electrode current collector. The packing density of the negative electrode active material layer was 1.20 g / cm. 3 It was.

[0067] A lead was attached to each of the positive and negative electrodes prepared above. A single-layer polypropylene separator was prepared. The positive and negative electrodes were alternately stacked one by one with the separators interposed therebetween to prepare a laminated electrode body.

[0068] A mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and methyl acetate in a volume ratio of 25:35:40-x:x was prepared. Vinylene carbonate was dissolved in this mixed solvent at a concentration of 1 mass%, lithium bis(oxalate)borate was dissolved in a concentration of 0.8 mass%, and LiPF6 as a supporting salt was dissolved in a concentration of 1.15 mol / L. This resulted in a nonaqueous electrolyte.

[0069] The laminated electrode body and the non-aqueous electrolyte solution thus prepared were placed in a square battery case and sealed to obtain a square lithium ion secondary battery for evaluation. The amount of the non-aqueous electrolyte solution injected was 9.0 g / Ah.

[0070] <Output evaluation - Output resistance measurement> Each evaluation lithium-ion secondary battery was adjusted to a SOC (State of charge) of 50% by constant current constant voltage (CC-CV) charging, and then placed in an environment of 25°C. Discharge was performed for 10 seconds at a current value of 40C, and the voltage rise amount ΔV at this time was obtained. The output resistance value of each evaluation secondary battery was calculated using this voltage rise amount ΔV and the current value. The results are shown in Table 1.

[0071] <High-rate cycle characteristic evaluation> Each evaluation lithium-ion secondary battery was placed in an environment of 25° C. and subjected to CC-CV charging for 3 hours at a charging voltage of 4.15 V and a charging current of 0.5 C. Then, it was discharged at a constant current (CC) of 0.5 C to 2.5 V. The discharge capacity at this time was measured and used as the initial capacity.

[0072] Next, each evaluation lithium-ion secondary battery was placed in an environment of 75° C. Each evaluation lithium-ion secondary battery was charged to SOC 40%, and then subjected to 25 cycles of charge and discharge, with one cycle consisting of a 12C constant current charge for 1 minute and a 12C constant current discharge for 1 minute. After that, each evaluation lithium-ion secondary battery was discharged to SOC 0%.

[0073] The operation of charging to SOC 40%, charging and discharging 25 times, and discharging to SOC 0% was repeated 400 times. Thereafter, the discharge capacity after the charge and discharge cycle was measured in the same manner as the initial capacity. The capacity retention rate (%) was calculated by (discharge capacity after charge and discharge cycle / initial capacity) x 100. The results are shown in Table 1.

[0074] [Table 1]

[0075] As shown in the results in Table 1, in Examples 1 to 4, which used CNT as the conductive material of the positive electrode and 2 to 9 volume % of methyl acetate as the nonaqueous solvent of the nonaqueous electrolyte, both low output resistance and high capacity after repeated charging and discharging at a large current were achieved. That is, in Examples 1 to 4, both high output characteristics and high resistance to capacity degradation when repeatedly charged and discharged at a large current were achieved.

[0076] In particular, Comparative Examples 3 to 5 are examples of the prior art that use acetylene black, which is a common conductive material for the positive electrodes of non-aqueous electrolyte secondary batteries. Comparing Comparative Examples 3 to 5 with Examples 1 to 4, it can be seen that the effect of improving the output characteristics and the effect of improving resistance to capacity degradation when repeatedly charged and discharged at a large current obtained in Examples 1 to 4 are significantly high. On the other hand, the results of Comparative Example 1 show that the improvement in output characteristics is insufficient when only CNTs are used without using methyl acetate.

[0077] [Examples 5 to 7 and Comparative Examples 6 to 10] A square-shaped lithium ion secondary battery for evaluation was obtained in the same manner as above, except that methyl propionate was used instead of methyl acetate as a non-aqueous solvent. The output characteristics and high-rate cycle characteristics of the obtained lithium secondary battery for evaluation were evaluated in the same manner as above. The results are shown in Table 2.

[0078] [Table 2]

[0079] As shown in the results of Table 2, the same results as those of Table 1 were obtained even when methyl propionate was used instead of methyl acetate. This shows that a carboxylate with a relatively small molecular size can provide an effect of improving output characteristics and an effect of improving resistance to capacity degradation when repeatedly charged and discharged at a large current. Therefore, it is clear that the nonaqueous electrolyte secondary battery disclosed herein is excellent in both output characteristics and resistance to capacity degradation when repeatedly charged and discharged at a large current.

[0080] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above.

[0081] That is, the nonaqueous electrolyte secondary battery disclosed herein has the following features [1] to [5]. [1] A positive electrode, A negative electrode; A non-aqueous electrolyte; A non-aqueous electrolyte secondary battery comprising: the positive electrode comprises a positive electrode current collector and a positive electrode active material layer supported on the positive electrode current collector, The positive electrode active material layer contains a positive electrode active material and carbon nanotubes, The non-aqueous electrolyte contains a non-aqueous solvent and a supporting salt, The non-aqueous solvent contains 2 to 9 volume % of a carboxylic acid ester having 6 or less carbon atoms which may be substituted with a fluorine atom. Nonaqueous electrolyte secondary battery. [2] The nonaqueous electrolyte secondary battery according to item [1], wherein the carbon nanotubes are multi-walled carbon nanotubes. [3] The nonaqueous electrolyte secondary battery according to item [1] or [2], wherein the carboxylic acid ester has 4 or less carbon atoms. [4] The nonaqueous electrolyte secondary battery according to any one of items [1] to [3], wherein the nonaqueous solvent contains 3 to 8 volume % of a carboxylic acid ester having 6 or less carbon atoms which may be substituted with a fluorine atom. [5] The nonaqueous electrolyte secondary battery according to any one of items [1] to [4], which is used as a vehicle driving power source for a hybrid vehicle. [Explanation of symbols]

[0082] 20 Wound electrode body 30 Battery case 36 Safety valve 42 Positive terminal 42a Positive current collector 44 Negative terminal 44a Negative current collector plate 50 Positive electrode sheet (positive electrode) 52 Positive electrode current collector 52a Portion where positive electrode active material layer is not formed 54 Cathode active material layer 60 Negative electrode sheet (negative electrode) 62 Negative electrode current collector 62a Part where negative electrode active material layer is not formed 64 Negative electrode active material layer 70 Separator sheet (separator) 80 Nonaqueous electrolyte 100 Lithium-ion secondary battery

Claims

1. A positive electrode and A negative electrode; A non-aqueous electrolyte; A non-aqueous electrolyte secondary battery comprising: the positive electrode comprises a positive electrode current collector and a positive electrode active material layer supported on the positive electrode current collector, The positive electrode active material layer contains a positive electrode active material and a conductive material, the conductive material is composed only of carbon nanotubes, The non-aqueous electrolyte contains a non-aqueous solvent and a supporting salt, the non-aqueous solvent contains 2 to 9 volume % of a carboxylic acid ester having 6 or less carbon atoms which may be substituted with a fluorine atom; Non-aqueous electrolyte secondary battery.

2. 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein the carbon nanotubes are multi-walled carbon nanotubes.

3. 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein the carboxylate ester has 4 or less carbon atoms.

4. 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein the nonaqueous solvent contains 3 to 8 volume % of a carboxylic acid ester having 6 or less carbon atoms which may be substituted with a fluorine atom.

5. 2. The nonaqueous electrolyte secondary battery according to claim 1, which is used as a vehicle driving power source for a hybrid vehicle.

Citation Information

Patent Citations

  • A high-rate lithium iron phosphate polymer battery

    CN109103490A

  • Lithium secondary battery

    JP2002305035A

  • Nonaqueous electrolyte battery

    JP2004047131A

  • Nonaqueous electrolyte battery

    JP2008181884A

  • Nonaqueous electrolyte secondary battery

    JP2019145448A